Understanding Work Meaning in Generation Z and Its Implications for Character Education - Apri Winge Adindo; Sutoyo Sutoyo (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
The rapid transformation of the labor market in the digital era has significantly influenced how young generations interpret work. As digital natives, Generation Z demonstrates distinct work orientations shaped by technological advancement, flexibility, and personal fulfillment. Understanding the meaning of work among Generation Z is essential, particularly in relation to strengthening character education as a foundation for future human resources development. This study aims to analyse how Generation Z in Surakarta interprets the meaning of work and to examine its implications for character education. This research employed a qualitative approach using in-depth interviews, observation, and documentation as data collection techniques. Informants were selected through purposive sampling to ensure relevance to the research focus. Data were analysed through thematic interpretation to identify patterns related to work orientation and value construction. The findings reveal that Generation Z predominantly interprets work as a calling rather than merely a job or career path. Work is perceived as an expression of personal interest, passion, and self-actualization. Consequently, they tend to avoid rigid and long-term employment structures that restrict flexibility and creativity. The study further identifies three major implications for character education: enhancing students’ capacity for reflective career decision-making, strengthening their ability to differentiate between needs and desires, and fostering responsibility and commitment in task completion. These findings underline the importance of integrating work-meaning perspectives into character education to prepare Generation Z for adaptive and value-driven professional engagement.